Naso-intestinal versus gastric tube for enteral nutrition in patients undergoing mechanical ventilation: a systematic review and meta-analysis - Chuanjin Liu; Junxun Jiang; Zunjia Wen; Tao You (Systematic Reviews)
Abstract Background A systematic appraisal of the comparative efficacy and safety profiles of naso-intestinal tube versus gastric tube feeding in the context of enteral nutrition for mechanically ventilated (MV) patients is imperative. Such an evaluation is essential to inform clinical practice, ensuring that the chosen method of nutritional support is both optimal and safe for this patient population. Methods We executed an exhaustive search across PubMed et al. databases to identify randomized controlled trials (RCTs) that scrutinize the role of naso-intestinal and gastric tubes for mechanically ventilated (MV) patients up to May 30, 2024. The process of study selection, quality assessment, and data extraction was conducted independently by two researchers. RevMan 5.3 software was used for meta-analysis. Results Our meta-analysis included 8 RCTs, published between 1992 and 2018, encompassing a total of 676 MV patients. The results indicated that naso-intestinal tube feeding, compared to gastric tube feeding, was associated with a significant reduction in the incidence of ventilator-associated pneumonia (VAP) [Risk Ratio (RR) = 0.69, 95% confidence interval (CI) (0.52, 0.92)] and gastric retention (RR = 0.11, 95% CI (0.04, 0.28)). No statistically significant differences were observed in the incidence of aspiration (RR = 0.93, 95% CI (0.35, 2.50)) vomiting (RR = 0.70, 95% CI (0.23, 2.08)), abdominal distension (RR = 0.87, 95% CI (0.29, 2.63)), or diarrhea (RR = 1.10, 95% CI (0.77, 1.55)). Conclusions The current evidence indicates that naso-intestinal tube feeding is efficacious in lowering the incidence of VAP and gastric retention among MV patients, without a corresponding escalation in the risk of adverse events, including aspiration, vomiting, abdominal distension, and diarrhea. These insights significantly augment the existing corpus of knowledge pertaining to the optimization of enteral nutrition strategies for patients on mechanical ventilation.